Prenatal diagnosis of two cases of congenital systemic venus return anomalies: A rare entity (Spain) (Archives of Pediatrics of Uruguay, 2023)
Introduction: anomalies in the development of the systemic venous system are a rare entity, and its prenatal and postnatal echocardiographic diagnosis can be challenging, due to its low incidence as well as to the difficulty in correctly performing echocardiographic imaging planes. However, its diagnosis is key because it is linked to congenital heart disease or chromosomal anomalies.Objective: describe two cases of a rare cardiovascular congenital anomaly. The persistence of the left superior vena cava with agenesis of the right superior vena cava is one of these described anomalies, with very low incidence when both variations occur together.Clinical cases: we present two cases of newborns with no relevant personal or family history, diagnosed prenatally with confirmed echocardiographic findings in the postnatal period.Conclusions: given the isolated finding in the fetal period of this anatomical variation that associates two anomalies of the systemic venous system, we should note the importance of its postnatal echocardiographic confirmation to rule out congenital heart disease that is difficult to diagnose during the prenatal period. Likewise, prior to the echocardiographic confirmation carried out by the pediatric cardiologist, we should stress the importance of the pediatrician diagnosis in the first physical examination and of the family history to rule out possible critical congenital heart disease or possible associated syndromes. The prenatal diagnosis of VCSIP with agenesis of the VCSD will lead to a high degree of suspicion of these associated pathologies and therefore may lead to early clinical action.
Keywords: Systemic venous development; Congenital abnormalities; Prenatal diagnosis